2021
DOI: 10.1007/s12161-021-02175-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydrophilic and Lipophilic Antioxidant Capacity in Spanish Tomato Paste: Usefulness of Front-Face Total Fluorescence Signal Combined with Parafac

Abstract: The hydrophilic and lipophilic antioxidant activities due to the main bioactive components present in Spanish tomato paste samples were studied, using standardized and fluorescent methods. After extraction, phenolic antioxidants (Folin-Ciocalteu method) and total antioxidant activity (TEAC assay) were evaluated, examining differences between hydrophilic and lipophilic extracts corresponding to different samples. Total fluorescence spectra of extracts (excitation-emission matrices, EEMs) were recorded in the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, another fluorescence index BGF_UV, which refers to the blue/green fluorescence induced by 375 nm UV light, was observed to display a decreasing trend during ripening in the study of Kim et al (2019). The BGF_UV is most likely to be related with flavonoids (Lai et al, 2007;Pardo-Botello et al, 2022), which were reported to increase during ripening in another study where the same tomato species was used (Bhandari & Lee, 2016). Further study is needed to investigate the reason for the occurrence of the blue-green fluorescence induced by red light and verify the changing pattern of the BGF_UV index during tomato ripening.…”
Section: Flexible In Geometrymentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, another fluorescence index BGF_UV, which refers to the blue/green fluorescence induced by 375 nm UV light, was observed to display a decreasing trend during ripening in the study of Kim et al (2019). The BGF_UV is most likely to be related with flavonoids (Lai et al, 2007;Pardo-Botello et al, 2022), which were reported to increase during ripening in another study where the same tomato species was used (Bhandari & Lee, 2016). Further study is needed to investigate the reason for the occurrence of the blue-green fluorescence induced by red light and verify the changing pattern of the BGF_UV index during tomato ripening.…”
Section: Flexible In Geometrymentioning
confidence: 91%
“…(2019). The BGF_UV is most likely to be related with flavonoids (Lai et al., 2007; Pardo‐Botello et al., 2022), which were reported to increase during ripening in another study where the same tomato species was used (Bhandari & Lee, 2016). Further study is needed to investigate the reason for the occurrence of the blue‐green fluorescence induced by red light and verify the changing pattern of the BGF_UV index during tomato ripening.…”
Section: Application Of Commercially Available Devices In the Food In...mentioning
confidence: 99%